Variation in auxin sensing guides AUX/IAA transcriptional repressor ubiquitylation and destruction - Martin Winkler (Nature Portfolio, 2017)
The phytohormone auxin is sensed by SCFTIR1-AUX/IAA receptors leading to AUX/IAA repressor ubiquitylation and turnover. Here the authors show that IAA6 and IAA19 differ in their ubiquitylation and turnover dynamics, differentially contributing to auxin sensing and enabling discrimination of auxin concentrations.